Heilige und Heiden im legendarischen Erzählen des 13. Jahrhunderts Formen und Funktionen der Aushandlung des religiösen Gegensatzes zum Heidentum - Prautzsch, Felix (Literatur - Theorie - Geschichte, 2021)
Against the backdrop of 13th-century cultural history, the study examines the function of legendary narratives in Christian identity formation. Martyrdom, war, and conversion are the basic narratives in negotiating religious opposition to heathendom. These stories were handed down from the early beginnings of Christianity and specifically updated in the context of crusades and missions.